GIS Development to Become an Income Generating Unit at UNWAHA Jombang - Edi Purnomo; Arivatu Ni’mati Rahmatika (INCOME: Innovation of Economics and Management, 2022)
Investment, literally is saving money with the aim of obtaining an expected return that is greater than deposit interest to meet the objectives to be achieved within a predetermined period of time and in accordance with the ability to capital, or it can also be interpreted as a sacrifice in the form of delaying current expenditures for get a better return in the future. (Putranto, 2016). The Islamic capital market is a capital market that is in accordance with Islamic sharia or in other words, the instruments used are based on sharia principles and the mechanisms used are also not Contrary to sharia principles. UNWAHA as one of the campuses in Jombang district which currently has an investment gallery that has been shaded by the OJK and cooperates with a securities company that provides a means of selling and buying sharia shares. UNWAHA Jombang is the 30th campus of universities in Indonesia that has open a sharia investment gallery to the public. The opening of this sharia investment gallery is carried out to fulfill the wishes of various parties, especially in terms of buying and selling sharia shares, as well as to fulfill a very important need as a means to carry out the practice of buying and selling shares which has become a lifestyle today.